1995
DOI: 10.1016/s0006-3495(95)79953-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of microtubule catastrophe assessed by probabilistic analysis

Abstract: Microtubules are cytoskeletal filaments whose self-assembly occurs by abrupt switching between states of roughly constant growth and shrinkage, a process known as dynamic instability. Understanding the mechanism of dynamic instability offers potential for controlling microtubule-dependent cellular processes such as nerve growth and mitosis. The growth to shrinkage transitions (catastrophes) and the reverse transitions (rescues) that characterize microtubule dynamic instability have been assumed to be random ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
146
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(161 citation statements)
references
References 38 publications
(47 reference statements)
14
146
0
1
Order By: Relevance
“…It has been shown experimentally, first by Odde et al [24] and more recently by Stepanova et al [25] and Gardner et al [26] that microtubule catastrophes have a certain historydependence, i.e., the probability for a microtubule to undergo catastrophe appears to depend on how long its has been growing. Based on these observations, it was suggested that catastrophe is a multi-step process, which requires a certain number of events to occur for its materialization.…”
Section: Results Ii: Microtubule Catastrophementioning
confidence: 99%
“…It has been shown experimentally, first by Odde et al [24] and more recently by Stepanova et al [25] and Gardner et al [26] that microtubule catastrophes have a certain historydependence, i.e., the probability for a microtubule to undergo catastrophe appears to depend on how long its has been growing. Based on these observations, it was suggested that catastrophe is a multi-step process, which requires a certain number of events to occur for its materialization.…”
Section: Results Ii: Microtubule Catastrophementioning
confidence: 99%
“…Analysis of filament lifetimes by using catastrophe time was conducted in analogy to Gardner et al (19). According to Odde et al (43,44), they can be described by using a gamma distribution where the predicted number of catastrophes at a given time t are dFnðtÞ dt = r n t n-1 e -rt ΓðnÞ dFnðtÞ dt = r n t n−1 e −rt ΓðnÞ ðprobability density functionÞ.…”
Section: Tirf Image Analysismentioning
confidence: 99%
“…The frequency at which a growing MT tip switches to a shortening state is called the "catastrophe" frequency, while "rescue" frequency is the frequency at which a shortening MT tip switches into a growing state [2]. Numerous studies using light microscopy have quantitatively characterized this behavior both in vitro and in vivo [3][4][5].…”
Section: Introductionmentioning
confidence: 99%